The Relation between Crude Oil Price and Government Expenditure in Libya: A VAR Approach. - المبروك, أ. نصر حسين محمود; علي, أ. محمد عبدالحفيظ محمد; الرفـادي, أ. محمد إبراهيم صـالـح (Dirasat in Economics and Business, 2022)
This study seeks to analyze the relationship between gove-rnment spending in Libya and international oil prices, by trac-king data across a time series that extends from 1980 to 2020 by following the method of des-criptive analysis by reviewing the most important public fina-ncial indicators in Libya, their developments and aspects of government spending during the study period. By following the descryiptive analysis method by reviewing the most important indicators of public finance in Libya and their developments and aspects of government spe-nding during the study period, as well as by following the stand-ard analysis using the Autor-egressive Vector Model VAR. The results showed the existence of a ''positive'' direct relation-nship between global oil prices and government spending in Li-bya and the presence of an effect For government spending in the previous year, the results were in line with the study's hypothe-ses and economic theory, with good statistical significance.